THE EFFECT OF BEND ANGLE ON THE EVAPORATIVE COOLING OF AIR FLOW THROUGH BENT DUCT (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
One remediation to output power drop of a gas turbine generating units during hot climates is reducing compressor inlet air temperature using fogging technique incorporating water injection into the airstream. The inlet air ductworks often include a bend or curved duct before the compressor comprising the secondary flow utilized to enhance the mixing between air and water droplets. This study investigates the effect of changing the bend angle on the resultant evaporative cooling of steadily flowing airstream. The experiments were conducted with an average air velocity range from (2.5 to 5 m/s) through (50) cm square duct. The study considered three bend angles of (45°, 90° and 135°) along with three sets of nozzle tilt angles of (- 45o, 0° and 45° ) to the axial flow direction. The results reveal that best evaporative cooling was achieved at a bend angle of (135°) when the water is axially injected, i.e., at (0o) to flow direction. These conditions were obtained at the velocity of (2.5 m/s), giving enough residence time for the injected droplets to evaporate and cool the airstream.